ACTI ON OF N- ACETYLCYSTEI NE ON ASYMMETRI C DIMETHYLARGININE AND ALBUMINURIA IN STAGE 1-4 NONDIABETIC CHRONIC KIDNEY DISEASE PATIENTS - THAHA, MOCHAMMAD; Widodo, Widodo; Yogiantoro, Moh.; NILAMSARI, WENNY PUTRI; YUSUF, MOCHAMAD; Tomino, Yasuhiko (Institute of Topical Disease Universitas Airlangga, 2010)
Background: Uremic patients are in a pro-oxidant state and show an increased level of asymmetric dimethylarginine (ADMA), which is due to increased PRMT1 activity and reduced dimethylarginine dimethylaminohydrolase (DDAH) as degradation enzymes. Reactive oxidant species may play an important role in increasing the action of PRMT1 and in inhibiting the action of DDAH. Albuminuria and ADMA are closely correlated with progression of cardiovascular disease in chronic kidney disease (CKD) patients as well as indicators for decreasing renal function. Although ACEIs and/or ARBs reduced albuminuria in CKD patients, the results are still conflicting. Several factors in these patients may play important roles in the mechanism of albuminuria such as oxidative stress. The antioxidant N-acetylcysteine may prove to have beneficial therapeutic effect, because it can reduce oxidative stress as shown by evidence in humans, and subsequently increase ADMA. The objective of the present study is to explore the contribution of the antioxidant N-acetylcysteine (NAC) to the decrease of ADMA and albuminuria in non-diabetic CKD patients. Material and Methods: Patients with non-DM CKD stage 1–4 with albuminuria were randomized to receive ACEI and/or ARB alone (control group) or with antioxidant NAC 600 mg orally twice a day (treatment group). Observations were performed for 3 months to measure ADMA and albuminuria before and after-treatment. 80 patients in total 40 in the control group and 40 in the treatment group were used. Results: After oral treatment with NAC, the plasma level of ADMA in the treatment group increased from 0.604 µmol/l to 0.689 µmol/l, whereas ADMA level in the control group exhibited a higher increase from 0.561 µmol/l to 0.743 µmol/l. The increases in these groups were significantly different (p < 0.02). Moreover, the level of albuminuria was reduced from 148.12 µg/mg • cr to 132.7 µg/mg • cr in the treatment group, and from 75.25 µg/mg • cr to 71.85 µg/mg • cr in the control group. The difference was significant (p < 0.001). Conclusion: The anti-oxidant N-acetylcysteine can be used as adjuvant therapy to inhibit the progression of CKD in patients by decreasing the ADMA level and albuminuria.